小说《后宫·甄嬛传》中的花卉意象解析 = Analysis of flower image in Chinese novel legend of Zhenhuan - 陈淽偌 Tan, Jee Yue (Nanyang Technological University, 2021)
于2010年出版的小说《后宫·甄嬛传》经改编成电视剧播出后，即引起了极大的反响。它之所以能够在当时古装剧泛滥的情况下脱颖而出，并得到极高的赞誉，除了制作团队的专业与敬业、跌宕起伏且紧凑的剧情等条件，也离不开原著小说的成功。作者流潋紫在情节中加入大量的花卉意象，本文意在探讨作者如何以花朵塑造小说中的人物与情节。 本文第一章整理《甄嬛传》中各人物与对应花卉，以此为基础，比较各个角色的性格与命运。第二章介绍《甄嬛传》中宫廷生活的花卉应用：御膳、衣饰纹样，剖析其在故事中所隐含的意蕴如何推动情节发展。第三章分析《甄嬛传》中如何应用花卉意涵塑造人物与情节，进而探讨这种应用的遗憾之处以及促使遗憾发生的原因。 关键词：《后宫·甄嬛传》；花卉意象；宫廷生活；花卉意涵 The television drama adaptation of the Chinese novel Legend of Zhenhuan has received great response ever since its release in 2010. The drama has managed to stand out from among the crowd of Chinese costume dramas and gain immense recognition, not only due to the dedication and professionalism of the cast and crew, the compact and complex plot, and other factors, but also through the success of the original novel material. As the author Liu Lianzi integrates flower imagery into the story, this thesis therefore intends to explore how her use of flowers shape the characters and plot in the novel. The first chapter of this thesis will compare each character to their destiny by sorting out the characters and corresponding flowers in Legend of Zhenhuan. The second chapter will introduce how flowers are applied in court life in Legend of Zhenhuan through imperial meals and clothing patterns, analyze how their implied meaning in the story promotes the development of the plot. The third chapter will analyze flower implications that portray the characters and develop the plot in Legend of Zhenhuan. This chapter will also explore the imperfections caused by the flower implications and the reasons for imperfections. Keywords: Legend of Zhenhuan, Flower Image, Palace Life, Flower Implications